THEATRICAL TECHNOLOGY IN TEACHING - Vera G. Pukhalskaya; Anna Yu. Kulinkovich (Высшее образование в России)
The article highlights the important aspects of a lecturer’s work on the text of a lecture including pronunciation, diction, vocal variety, and gestures. The article adduces advice of the renowned stage masters and public speakers on the rules for preparing a successful public speech.